CLEANING OF THE POLLUTED PONDS WITH SOME WATER PLANTS (Experimental biology, 2016)
In article pollution level is determined by heavy metals of the polluted ponds. Prevention of pollution of water it is actual today. As model experiment for purification of the polluted waters some water activities of a plant were selected. For biological cleaning of a water as Eichhórnia crássipes and Pistia stratiotes were used.Water hyacinths are considered as fitoremediator which are used for cleaning of the polluted lakes and the rivers of heavy metals and biogenous elements. In experiment influence of biogenous elements on concentration of biomass of water hyacinths was defined. Our purpose consists in findings of an optimum biological way for purification of the polluted pond water by means of water hyacinths of Eichhórnia crássipes, Lemna minor and Pistia stratiotes. It was originally defined concentration of metals in water, the ambassador in the polluted water water hyacinths were grown up, and it was investigated the level of biosorptions. Concentration of metals in water decided on the help of AAS.
Keywords: heavy metals; IZV; maximum concentration limit; AAS; biosorption; stability; biogenous elements; biomass; allelopatiya.